Investigating the effect of liquid viscosity on two-phase gas-liquid flows - Abdulahi, Abolore (2014)
Simultaneous flow of gas-liquid in pipes presents considerable challenges and difficulties due to the complexity of the two-flow mixture. Oil-gas industries need to handle highly viscous liquids, hence studying the effect of changing the fluid viscosity becomes imperative as this is typically encountered in deeper offshore exploration. This work looks at the effect of liquid viscosity on gas-liquid flows. The work was carried out using two different pipes of 67mm and 127mm internal diameter. For the experiments carried out on the 67mm diameter pipe, air and three different liquids were used with viscosities 1, 42 and 152cp. With these experiments, the effect of viscosity on the entrainment process from the Taylor bubble in a vertical tube was investigated with the Taylor bubble being held stationary in a downward liquid flow with the use of three different gas injection methods. Taylor bubble length, the gas flow rate and the liquid flow rate approaching the stationary bubble were varied. In addition, the wake length below the stationary bubble was measured at different conditions of gas and liquid superficial velocities and comparison was made with the work by previous authors. Videos were taken with high speed camera to validate the measurement taken on wake lengths. A Wire Mesh Sensor system was placed at two different positions below the air injection point on the 67mm diameter pipe of the stationary bubble facility whose data acquisition provided time and cross-sectionally resolved information about spatial distribution. This information was used to generate time averaged void fraction, bubble size distribution and contour plots of the two-phase flow structure. A Probability Density Function (PDF) of void fraction can be obtained from the former, with PDFs of the wake section of the stationary bubbles showing that the flows are in the bubbly region while the PDF for the entire slug unit assumed that for a typical twin-peaked slug flow. The interpretation of this is that holding a bubble stationary can simulate real slug flow. Results on the bubble length measurement and gas loss into a bubble wake have shown good agreement with existing work by other authors. Experiments on the 127 mm diameter pipe were carried out because most published work on gas/liquid flow were on smaller diameter pipes with air and water, yet many of the industrial applications of such flows in vertical pipes are in larger diameter pipes and with liquids which are much more viscous than water. Another important parameter considered in the study is pressure because of its effect on gas density. This part of the research goes some way to rectify this lack and presents void fraction and pressure gradient data for sulphur hexafluoride with gas densities of 28 and 45 kg/m3 and oil (viscosity 35 times water). The gas and liquid superficial velocities were varied in the ranges 0.1-3 and 0.1-1 m/s respectively. The void fraction was also measured with a Wire Mesh Sensor system. Flow patterns were identified from the signatures of the Probability Density Function of cross-sectionally averaged void fraction. These showed the single peak shapes associated with bubbly and churn flow but not the twin-peaked shape usually seen in slug flow. This confirms previous work in larger diameter pipes but with less viscous liquids. For the bubble to churn flows investigated, the pressure gradients decreased with increasing superficial gas velocity. The change in pressure ultimately affects the density of gas in the two-phase flow mixture. Though there was little effect of pressure on void fraction below certain transitional flow rates, the effect became significant beyond these values. Different statistical analysis techniques such as power spectral density, probability density function, mean, standard deviation and time series of the acquired data have been used which also show the significant effect of pressure on void fraction at high gas density which have not been measured previously.